Saturation of Specific Absorption Rate for Soft and Hard Spinel Ferrite Nanoparticles Synthesized by Polyol Process - Cristian Iacovita; Gabriela Fabiola Stiufiuc; Roxana Dudric; Nicoleta Vedeanu; Romulus Tetean; Rares Ionut Stiufiuc; Constantin Mihai Lucaciu (Magnetochemistry, 2020)
Spinel ferrite nanoparticles represent a class of magnetic nanoparticles (MNPs) with enormous potential in magnetic hyperthermia. In this study, we investigated the magnetic and heating properties of spinel soft NiFe2O4, MnFe2O4, and hard CoFe2O4 MNPs of comparable sizes (12–14 nm) synthesized by the polyol method. Similar to the hard ferrite, which predominantly is ferromagnetic at room temperature, the soft ferrite MNPs display a non-negligible coercivity (9–11 kA/m) arising from the strong interparticle interactions. The heating capabilities of ferrite MNPs were evaluated in aqueous media at concentrations between 4 and 1 mg/mL under alternating magnetic fields (AMF) amplitude from 5 to 65 kA/m at a constant frequency of 355 kHz. The hyperthermia data revealed that the SAR values deviate from the quadratic dependence on the AMF amplitude in all three cases in disagreement with the Linear Response Theory. Instead, the SAR values display a sigmoidal dependence on the AMF amplitude, with a maximum heating performance measured for the cobalt ferrites (1780 W/gFe+Co), followed by the manganese ferrites (835 W/gFe+Mn), while the nickel ferrites (540 W/gFe+Ni) present the lowest values of SAR. The heating performances of the ferrites are in agreement with their values of coercivity and saturation magnetization.